Structural insights and biomedical potential of biosynthesized silver nanoparticles: antibacterial activity, anti-biofilm and cancer cell inhibition - Jemel, Ikram; Krayem, Najeh; Jlidi, Hajer; Ben Bacha, Abir; Alonazi, Mona; Charguia, Raihane; Alzahrani, Areej Ali; Aifa, Sami; Mnif, Sami (PeerJ, 2025)
Background The increasing threat of antimicrobial resistance and cancer has driven the search for new therapeutic agents, with plant-based biosynthesis of nanoparticles emerging as a promising approach. Silver nanoparticles (AgNPs) synthesized from plant extracts have gained attention for their potential biomedical applications. Objective This study aimed to synthesize, characterize, and evaluate the antimicrobial, anti-biofilm, and anticancer properties of AgNPs derived from Teucrium polium (Tp), Teucrium marum (Tm), and Punica granatum (Pg). Methods AgNPs were synthesized using plant extracts and characterized by X-ray diffraction (XRD), dynamic light scattering (DLS), UV spectroscopy, and Fourier-transform infrared spectroscopy (FTIR). Antibacterial activity was assessed against Gram-negative and Gram-positive bacteria. The anti-biofilm efficacy was tested against Staphylococcus aureus and Pseudomonas aeruginosa. Cytotoxicity was evaluated on MCF-7 breast cancer cells. Results XRD confirmed the face-centered cubic (fcc) crystal structure of AgNPs, with peaks at (111), (200), (220), and (311) planes. Crystallite sizes were smaller than their hydrodynamic diameters, suggesting surface modifications affecting DLS measurements. DLS analysis indicated monodisperse size distributions for Tp-AgNPs and Tm-AgNPs, while Pg-AgNPs showed a broader range. The biosynthesized silver AgNPs from different plants exhibit unique physicochemical properties, as evidenced by their distinct UV-vis absorption spectra, and show potential for optical and optoelectronic applications. FTIR spectroscopy analysis confirmed the presence of specific functional groups on the surface of biosynthesized AgNPs, indicating the role of plant extracts as reducing and capping agents, and revealed variations in binding sites and molecular interactions. Among the synthesized nanoparticles, Tp-AgNPs exhibited the highest antibacterial efficacy, particularly against Staphylococcus epidermis and Pseudomonas aeruginosa, though slightly less potent than chloramphenicol. Tp-AgNPs also showed the strongest inhibition of biofilm formation, followed by Tm-AgNPs, with Pg-AgNPs being the least effective. Cytotoxicity assays demonstrated that Tm-AgNPs had the highest anticancer activity against MCF-7 cells, with Tp-AgNPs exhibiting comparable effects. Conclusion The findings underscored the potent antimicrobial, anti-biofilm, and anticancer properties of Tp-AgNPs and Tm-AgNPs, making them promising candidates for biomedical applications. Further studies are needed to assess their clinical safety and therapeutic potential.
Keywords: Plant extracts; Antibacterial activity; Anti-biofilm; Cancer cell inhibition; Nanotechnology; Silver nanoparticles